2018
DOI: 10.5194/angeo-36-541-2018
|View full text |Cite
|
Sign up to set email alerts
|

New results on the mid-latitude midnight temperature maximum

Abstract: Abstract. Fabry–Perot interferometer (FPI) measurements of thermospheric temperatures and winds show the detection and successful determination of the latitudinal distribution of the midnight temperature maximum (MTM) in the continental mid-eastern United States. These results were obtained through the operation of the five FPI observatories in the North American Thermosphere Ionosphere Observing Network (NATION) located at the Pisgah Astronomic Research Institute (PAR) (35.2∘ N, 82.8∘ W), Virginia Tech (VTI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The strong equatorward winds that often precede the MTM can form a converging wind pattern over the latitude range (±30 • ) of these simulations. Note that this is not the same as the MTM-associated local converging wind analyzed by Mesquita et al (2018) using these data. Second, the sudden decrease in zonal winds, which is correlated with the MTM, can also enhance ESF growth (Huba et al, 2009).…”
Section: Accepted Articlementioning
confidence: 81%
See 3 more Smart Citations
“…The strong equatorward winds that often precede the MTM can form a converging wind pattern over the latitude range (±30 • ) of these simulations. Note that this is not the same as the MTM-associated local converging wind analyzed by Mesquita et al (2018) using these data. Second, the sudden decrease in zonal winds, which is correlated with the MTM, can also enhance ESF growth (Huba et al, 2009).…”
Section: Accepted Articlementioning
confidence: 81%
“…Observations of this MTM wind pattern have been recently obtained over a large region of North America, using the North American Thermosphere Ionosphere Observing Network (NATION; Mesquita et al, 2018). The regional-scale NATION wind dataset shows rapid changes in wind strength and direction.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed that MSTIDs rarely propagate to magnetic latitudes less than 15°, and it occurs during the low solar activity period. Narayanan et al (2014) pointed out two physical explanations for that: first, the increasing intensity due to midnight pressure bulge shift to the poles (further details about midnight pressure bulge can be found in Figueiredo, Buriti, et al, 2017;Mesquita et al, 2018) when MSTIDs occur late at night and second, when MSTIDs propagate before midnight, it encounters the equatorial ionization anomaly that limits its propagation toward the equator. Amorim, and Candido (2008), which presented velocities ranging from 50 to 100 m/s.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%